Evaluation of knowledge and attitudes of the faculty of medicine students about human papillomavirus infections, related cancers, and human papillomavirus vaccines - Zührenur Yağan; Aysun Aldanmaz; Tahir Ertuğrul; Zeynep Beyza Tolan; Adnan Menderes Bilgiç; Aslı Bilgiç (Galenos Publishing House, 2023)
Background and Design: The human papillomavirus (HPV) is a non-enveloped DNA virus infecting skin and mucosal surfaces and causes one of the most common sexually transmitted infections worldwide. Thus, physicians must know about HPV infections, associated cancers, and immunization for public health. This study aimed to determine the knowledge of medical faculty students about HPV infections, related cancers, and vaccines and examine related variables. Materials and Methods: This descriptive study included all students in the first to fifth grades of the faculty of medicine. Data were collected with a two-part questionnaire consisting of 37 questions. Questionnaires were filled voluntarily. Data were analyzed with SPSS version 18.0. Results: The study included 250 medical students, and 52.4% (n=131) were men. While 95.6% (n=239) stated that they were aware of HPV, only 39.2% thought that they had sufficient knowledge. The most important sources of information were lectures and the Internet. Only 3.6% (n=9) of the students had been vaccinated against HPV. The most important reason (58%) for not being vaccinated was not having heard of the HPV vaccine before or not knowing someone who had it, and the other important reason was economics. Nearly 80% of the students thought that HPV vaccines should be included in routine vaccination. While 60% of the students stated that they would get an HPV vaccine if a free vaccine is provided, the lack of sufficient information was cited as the most important reason (45%) against the widespread use. Conclusion: The knowledge of medical school students about HPV infection and vaccines was not very sufficient, and the vaccination rate was low. Our results suggest that HPV-related courses in medical education and reimbursement of vaccines by health authorities require some adjustments in the core education curriculum and national health policies.